Efek ekstrak bunga telang (Clitoria ternatea) sebagai anti bakteri alami terhadap pertumbuhan bakteri Staphylococcus aureus - Dyah Widhowati; Beti Gistawati Musayannah; Olan Rahayu Puji Astusi Nussa (VITEK : Bidang Kedokteran Hewan, 2022)
This research was conducted to determine the effect of the extract of telang flower (Clitoria ternatea) as a natural antibacterial on the growth of Stapylococcus aureus bacteria in terms of the results of the inhibition test and phytochemical screening. This study used 5 treatments with 5 replications in positive control and negative control, for the extract treatment using duplo replication. P0 as a positive control using Amoxicillin antibiotic, P0 as a negative control using a blank disk, P1 as a treatment using a telang flower extract with a concentration of 80%, P2 as a treatment using a telang flower extract with a concentration of 90%, and P3 a treatment using a telang flower extract with a concentration of 100 %. The results of the inhibition zone measurements showed the highest average in the positive control. The average diameter of the inhibition zone using the Agar Well Diffusion Method showed a significant difference (P<0.05). These results are supported by the ANOVA test with H1 accepted so that it can be said that there is an effect of telang flower extract (Clitoria ternatea) on the growth of Staphylococcus aureus bacteria. The results of phytochemical screening showed that the telang flower extract contained antibacterial active compounds, namely flavonoids, tannins, saponins, alkaloids, steroids and terpenoids.